THE ROLE OF HEALTH INFORMATION MANAGEMENT PROFESSIONALS IN THE IMPELENTATION OF INA-CBGs IN BLUD RSU H. BOEJASIN PELAIHARI - Dedy Kurniawan; - Hosizah (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2013)
ABSTRACTBackgrounds:Jamkesmas refers to medical assistance program designed to meet the needs of low income people which is funded by the federal goverment. The prospective payment systems is adopted as payment method is called an Indonesia Case Based Groups (INA-CBGs). In an INA-CBGs, an accurate and complete clinical data is required. While the primary function of health information department is providing that an accurate and complete clinical data for billing, In BLUD RSU H. Boejasin Pelaihari, HIM professional is not exist yet so provide clinical data for billing is carried out by other health workforce. No one of coders' process for review of clinical data, the billing process, and the payers' reimbursement to the healthcare facilities.Objectives:This study aims toinvestigate the role ofhealth informationmanagement professionals in INACBGs implementationMethods:This descriptive research study was performed to describe INA-CBGs implementation. The study population all of the health workforce involve in INA-CBGs implementation, sample are coder and independent verificator. An interview guide and checklist were used as instrument for observation and interview.Results:On the flow and procedures of INA-CBGs reimbursement process shows redundancy verification at claim document so take long times claim process. The three activities include data entry, grouping and recapitulation to be done of two health workforces, they are should be only done one health workforce.The eleven workforces in case-mix group member include hospital director, the head of services, the physicians, the head of medical record department, pharmacistand the services staff. Coded Diagnosis and procedures data is verified by independent verificator, whose not member of case-mix group. It is should not be needed, that is primary function of health information department or medical record department for providing accurate and complete clinical data for billing. The role a HIM professional are increase revenue potential by assuring accurate coding supported by documentation, improved cash flow by first time processing with few denials and appeals required etc.No case-mix team and no expenditure for them.Keywords: Health Information Management (HIM), HIM Professional, INA-CBGs, Medical Record, Reimbursement Process, Coder